Will Mobile Web Era impact the user’s behaviour in a digital library? - Scarnò, Marco; Sforzini, Donatella; Contino, Ugo; Gargiulo, Paola (Qualitative and Quantitative Methods in Libraries, 2017)
Almost 10 millions of articles were disseminated trough the web by CINECA.These are accessed by many academic Italian institutions located in the CentreSouth of Italy. In order to be prepared for the "Mobile Web Era", it was realized an optimized version of the website to facilitate the "experience of the mobile users". We analysed the behaviour of such users and of the standard ones; to do this we considered their "traces" stored into the web server log file. Some results are expected, like more browsing and less downloads; other surprising, like people that access the digital library only through a mobile device.